INDIKATOR PEMANTAUAN WILAYAH SETEMPAT KESEHATAN IBU DAN ANAK DI WILAYAH KERJA PUSKESMAS KARANGANYAR KABUPATEN PURBALINGGA TAHUN 2021 - Dhiah Farida Ariyanti; Tri Utami (Jurnal Kesehatan Masyarakat, 2022)
The maternal mortality ratio (MMR) and the infant mortality ratio is an indicator of public health status. In Purbalingga Regency, MMR is increased in three years. In 2021, MMR is estimated at 27 per 100.000 life births. The infant mortality ratio is increased in three years. In 2021, the infant mortality ratio is estimated as 9,7 per 100.000 life births.(1) In the work area Puskesmas Karanganyar, MMR is 0 in three years.(2) The infant mortality ratio in the puskesmas karanganyar is beyond the expected supposed 6 per 1000 live births, but the deaths are more than 6 per 1000 live births. A lot of factors affect the maternal mortality ratio and the infant mortality ratio, some of them are quality of antenatal care (ANC), quality of health services, quality of mother parturition services, quality of neonatal care, and detection of high-risk and complication obstetrics neonatal. This can be seen from the scope of Pemantauan Wilayah Setempat Kesehatan Ibu dan Anak (PWS KIA) indicators. In this paper, the method used is a case study. This is a case study aimed at describing the attainment of the PWS KIA in the work area of Puskesmas Karanganyar using seeing and analyzing data PWS KIA in 2021.(4)  The subject of this research is the secondary data on the PWS KIA indicators Puskesmas Karanganyar for the year 2021. The result of this research obtained for the attainment of the PWS KIA indicators on ANC (K4) as 92.6%, help childbirth at the health facilities at 96.6%, mother parturition services at 97.1%, neonatal care at 91%, detection of high-risk and complication obstetrics neonatal by health labor as 99.8% and by people as 49.5%. In the conclusion of this research, there is a gap in the K4 indicator at 5.4%, which helps the childbirth indicator at 3.4%, mother parturition services indicator (KF3) at 2.9%, neonatal care indicator at 9%, and detection of high-risk and complication obstetrics neonatal indicator by health labor at 0.2%. In the achievements of PWS KIA indicators, a lot of factors affect pregnant women, the midwife, and the community.